2009
DOI: 10.1111/j.1365-2621.2009.01993.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation study of gum extraction from Basil seeds (Ocimum basilicum L.)

Abstract: Basil seed (Ocimum basilicum L.) is cultivated in large quantities in different regions of Iran. This seed has reasonable amounts of gum with good functional properties which is comparable with commercial food hydrocolloids. A central composite rotatable design was applied to evaluate the effects of temperature, pH and water ⁄ seed ratio on the yield, apparent viscosity and protein content of water-extracted Basil seed gum. All of the variables significantly (P < 0.05) affected the extraction yield, whereas th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
115
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(122 citation statements)
references
References 19 publications
4
115
2
1
Order By: Relevance
“…Therefore, the fitted regression models were expressed as contour plots in order to visualize the relationship between the response variables and experimental levels of each factor and to deduce the optimum conditions. For graphical optimization, contours plots were plotted by keeping one variable constant at the center point and varying the other two variables within the experimental range (Razavi et al 2009;Mason et al 2003). In addition the desirability function was used for achieving optimization with multiple responses.…”
Section: Optimization Proceduresmentioning
confidence: 99%
“…Therefore, the fitted regression models were expressed as contour plots in order to visualize the relationship between the response variables and experimental levels of each factor and to deduce the optimum conditions. For graphical optimization, contours plots were plotted by keeping one variable constant at the center point and varying the other two variables within the experimental range (Razavi et al 2009;Mason et al 2003). In addition the desirability function was used for achieving optimization with multiple responses.…”
Section: Optimization Proceduresmentioning
confidence: 99%
“…At higher extraction temperatures the amount of protein is enhanced due to superior mass transfer rates; on the other hand, increasing extraction pH decreased protein content (Koocheki et al, 2008;Karazhiyan et al, 2010). On the other hand, research done by Razavi et al (2009), revealed that effect of extraction temperature on the protein was highly significant, which in a lower temperature led to a lower protein content and a higher purity, and the effect of pH was not significant. High protein content in mucilage is noteworthy due to protein content is known to have effects on the emulsifying behaviour.…”
Section: Chemical Propertiesmentioning
confidence: 99%
“…Mucilage extraction from O. basilicum seeds was carried out by a modified method of Razavi et al, [25] where 100 g of cleaned Ocimum seeds were allowed to soak in distilled water: Seed ratio of 10:1 (at 35°C for 12 h) and blended at 1500 rpm for 15 min to scrap the gum layer of the seed surface. Blended mass squeezed with many folds of muslin cloth to separate the mucilage.…”
Section: Extraction Of O Basilicum Seed Mucilagementioning
confidence: 99%